2013
DOI: 10.1007/s40544-013-0001-7
|View full text |Cite
|
Sign up to set email alerts
|

Hydration lubrication

Abstract: Abstract:The hydration lubrication paradigm, whereby hydration layers are both strongly held by the charges they surround, and so can support large pressures without being squeezed out, and at the same time remain very rapidly relaxing and so have a fluid response to shear, provides a framework for understanding, controlling, and designing very efficient boundary lubrication systems in aqueous and biological media. This review discusses the properties of confined water, which-unlike organic solvents-retains it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
429
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 460 publications
(444 citation statements)
references
References 117 publications
(116 reference statements)
11
429
3
1
Order By: Relevance
“…Phospholipids, bottle-brush glycoproteins, and linear polysaccharides have all been implicated, and the debate between scientists advocating different opinions 6,7 has at times been intense. It is nowadays clear that the key is the presence of a fluid water layer between the sliding surfaces that is maintained by the biolubricants, 8 and that synergies between different biolubricants need to be considered in order to capture the essence of biolubrication. For instance, it has been reported that addition of hyaluronan and phospholipids together is more effective in alleviating joint disease symptoms than any of these two components alone.…”
Section: Introductionmentioning
confidence: 99%
“…Phospholipids, bottle-brush glycoproteins, and linear polysaccharides have all been implicated, and the debate between scientists advocating different opinions 6,7 has at times been intense. It is nowadays clear that the key is the presence of a fluid water layer between the sliding surfaces that is maintained by the biolubricants, 8 and that synergies between different biolubricants need to be considered in order to capture the essence of biolubrication. For instance, it has been reported that addition of hyaluronan and phospholipids together is more effective in alleviating joint disease symptoms than any of these two components alone.…”
Section: Introductionmentioning
confidence: 99%
“…Water lubricants have greater potential for achieving superlubricity because of their low pressure-viscosity coefficients [11]. Klein et al obtained superlubricity between two mica surfaces lubricated by a surfactant layer and charged polymers at a nano-scale using a surface force apparatus (SFA) [12][13][14]. Kato et al obtained superlubricity between two ceramic surfaces (Si 3 N 4 /CN x /SiC) with water lubrication at a macro-scale using a traditional tribometer [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…However, some of the basic properties of hydration lubrication, such as the frictional energy dissipation, remain unclarified despite decades of study. In all relevant studies to date, the measured friction was dominated by other dissipation pathways, such as polymer chains disentangling from each other or the distortion of sheared liposomes [23]. Recently, Klein's group overcame these limitations by trapping hydrated ions in the gap between molecularly smooth surfaces, and measuring the friction between the surfaces as they slid at pressures and shear rates one or two orders of magnitude higher than those previously achieved.…”
Section: Liquid Superlubricitymentioning
confidence: 99%